Systematic analysis of circadian genes using genome-wide cDNA microarrays in the inflammatory bowel disease transcriptome. (August 2015) - Palmieri, Orazio; Mazzoccoli, Gianluigi; Bossa, Fabrizio; Maglietta, Rosalia; Palumbo, Orazio; Ancona, Nicola; Corritore, Giuseppe; Latiano, Tiziana; Martino, Giuseppina; Rubino, Rosa; Biscaglia, Giuseppe; Scimeca, Daniela; et al.
<x xml:space="preserve">Abstract</x> Simultaneous analysis of the transcripts of thousands of genes by cDNA microarrays allows the identification of genetic regulatory mechanisms involved in disease pathophysiology. The circadian clock circuitry controls essential cell processes and the functioning of organ systems, which are characterized by rhythmic variations with 24-hour periodicity. The derangement of these processes is involved in the basic mechanisms of inflammatory, metabolic, degenerative and neoplastic diseases. We evaluated by genome-wide cDNA microarray analysis the transcriptome of endoscopic mucosal biopsies of patients with inflammatory bowel diseases (IBD) focusing on the expression of circadian genes in Crohn's disease (CD) and ulcerative colitis (UC). Twenty-nine IBD patients (15 with CD and 14 with UC) were enrolled and mucosal biopsies were sampled at either inflamed or adjacent non-inflamed areas of the colon. A total of 150 circadian genes involved in pathways controlling crucial cell processes and tissue functions were investigated. In CD specimens 50 genes were differentially expressed, and 21 genes resulted up-regulated when compared to healthy colonic mucosa. In UC specimens 50 genes were differentially expressed, and 27 genes resulted up-regulated when compared to healthy colonic mucosa. Among the core clock genes ARNTL2 and RORA were up-regulated, while CSNK2B, NPAS2, PER1 and PER3 were down-regulated in CD specimens. Conversely, ARNTL2, CRY1, CSNK1E, RORA and TIPIN were up-regulated, while NR1D2 and PER3 were down-regulated in UC. In conclusion, in CD and UC patients there are differences in the expression of circadian genes between normal and diseased intestinal mucosa. The deregulated genes evidenced by transcriptome analysis in the major IBDs may play a crucial role in the pathophysiological mechanisms and may suggest novel therapeutic approaches.